La especialización hemisférica y la regulación de la conducta motora desde la perspectiva de la neurociencia cognitiva. - Machado, Sergio; Arias-Carrión, Oscar; Orellana Castillo, Alejandra Verónica; Lattari, Eduardo; Cardoso Silva, Adriana; Egídio Nardi, Antonio (Salud Mental)
Introduction Our understanding of functional brain organization is due to advances in neuroimaging technologies and intensive clinical research. Recently, cognitive science (cognitive neuroscience), combined with advances in technology, have changed our understanding of brain-behavior relationship. This symbiotic relationship has allowed a better characterization of the lesion site in patients with brain disorders and patterns of activation in healthy subjects. Objective In this article we discuss the contribution of the left hemisphere and right hemisphere involvement in the regulation of motor behavior; this will allow us to better understand the lateralization of motor functions. Development The results support the view of a left hemisphere dominance for language and motor control, and a right hemisphere dominance for spatial functions and attention. Specialized areas are probably predetermined and certain functions are lateralized to one or other hemisphere due to the efficient organization and information processing in the brain. Conclusion In the studies reviewed, specific functions for each hemisphere were observed, suggesting the existence of a complex organization that recruits several areas of the Nervous System for proper task performance.